Answer:
y = (C -0.99n)/48
Step-by-step explanation:
Undo what is done to y, in the reverse order. We have y multiplied by 48 then added to 0.99n. So, we must add the opposite of 0.99n and multiply that result by the reciprocal of 48.
C = 48y + 0.99n . . . . . . given
C - 0.99n = 48y . . . . . . add -0.99n
(C -0.99n)/48 = y . . . . . multiply by 1/48
Answer
5 and 90
Step-by-step explanation:
Answer:
I would stay direct vartation
Step-by-step explanation:
For example, if y varies directly as x, and y = 6 when x = 2, the constant of variation is k = = 3. Thus, the equation describing this direct variation is y = 3x.
Answer:
9 quizzes a week
Step-by-step explanation:
Answer:
152
Step-by-step explanation:
Hello there!
The prism shown is a triangular prism
There are many different formulas for solving for the surface area of a triangular prism but I am going to use the most simple one
Formula: SA = bh + L(s1 + s2 + s3) (found in the image)
b = base length
h = height
L = length
s1 = (same thing as the base length)
s2 and s2 = other triangle side lengths ( the base is an isosceles triangle so they are equal to each other.)
The triangular prism has the following dimensions
b = 6
h = 4
L = 8
s2 and s3 = 5
Now that we have identified each dimension we plug in the values into the formula
SA = 6*4 + 8(6+5+5)
6*4=24
8*6=48
8*5=40
40*2=80
80+48=128
128 + 24 = 152 so the surface area of the triangular prism is 152 cm²